Fewer daily steps are associated with greater cartilage oligomeric matrix protein response to loading post‐ACL reconstruction. Issue 10 (20th January 2022) - Davis‐Wilson, Hope C.; Thoma, Louise M.; Johnston, Christopher D.; Young, Emma; Evans‐Pickett, Alyssa; Spang, Jeffrey T.; Blackburn, J. Troy; Hackney, Anthony C.; Pietrosimone, Brian
Abstract: Aberrant joint loading contributes to the development of posttraumatic knee osteoarthritis (PTOA) following anterior cruciate ligament reconstruction (ACLR); yet little is known about the association between joint loading due to daily walking and cartilage health post‐ACLR. Accelerometer‐based measures of daily steps and cadence (i.e., rate of steps/min) provide information regarding daily walking in a real‐world setting. The purpose of this study was to determine the association between changes in serum cartilage oligomeric matrix protein (COMP; %∆COMP), a mechanosensitive biomarker that is associated with osteoarthritis progression, following a standardized walking protocol and daily walking in individuals with ACLR and uninjured controls. Daily walking was assessed over 7 days using an accelerometer worn on the right hip in 31 individuals with ACLR and 21 controls and quantified as mean steps/day and time spent in ≥100 steps/min. Serum COMP was measured before and following a 3000‐step walking protocol at a preferred speed. %∆COMP was calculated as a change in COMP relative to the prewalking value. Linear regressions were used to examine associations between daily walking and %∆COMP after adjusting for preferred speed. Fewer daily steps (Δ R 2 = 0.18, p = 0.02) and fewer minutes spent in ≥100 steps/min (Δ R 2 = 0.16, p = 0.03) were associated with greater %∆COMP following walking in individuals with ACLR; no statistically significant associations existed in controls (daily steps: Δ R 2 = 0.03, p = 0.47; time ≥100 steps/min: Δ R 2 < 0.01, p = 0.81). Clinical significance: Individuals with ACLR who engage in less daily walking undergo greater %ΔCOMP, which may represent greater cartilage degradation or turnover in response to walking.